Penguatan identitas nasional di era globalisasi: Tantangan dan strategi bangsa - chasib, muhammad - (Maliki Interdisciplinary Journal, 2025)
National identity is a vital pillar in safeguarding a nation’s existence and sovereignty, especially in the face of accelerating globalization. While globalization fosters openness and cultural exchange, it also poses a threat to the preservation of local and national values. This phenomenon raises concerns about the weakening of nationalism, particularly among the younger generation. This article aims to examine the challenges posed by globalization to Indonesia’s national identity and to formulate strategies for its reinforcement. The study employs a literature review method, drawing on academic sources published between 2019 and 2025. The findings indicate that key elements of Indonesia’s national identity—such as language, culture, religion, and the noble values of Pancasila—are increasingly under pressure from the dominance of foreign cultures and globalized lifestyles. The proposed strategies for strengthening national identity focus on character education rooted in Qur’anic values and personal responsibility, along with the integration of national education as outlined in Law No. 2 of 2003. Education plays a central role in shaping a generation that is not only intellectually capable but also morally grounded, spiritually devout, and proud to be part of the Indonesian nation. This effort must be continuously supported by families, educational institutions, and society at large.